O saber docente e as contribuições para a formação humana integral dos discentes do Curso Integrado de Agropecuária do IFAM Zona Leste - Medeiros, Carime Elias Araújo de (2020)
The main goal of the present work is to analyze how the teaching knowledge, linked to the pedagogical practice of the High School Vocational School (HSVS), contributes to the students' integral human formation from the integrated agriculture high School vocational course of the Federal Institute of Amazonas (IFAM). The specific objectives are: to identify the pedagogical knowledge used in the classroom at the vocational school; to enumerate the main difficulties found in the classroom for the students' integral human formation; to describe the possible pedagogical actions to be developed to improve teaching practice; to develop a product that favors the continuing education of teachers who work at HSVS and whose principle the integral human formation. This research was motivated by the following question: how is the teaching knowledge related to the students' integral human formation from the Integrated Agriculture course at the IFAM Campus Zona Leste? To answer this question, some questions were established: do the professionals working at the HSVS know the educational objectives that guide integrated high school education? Is continuing education a common practice among HSVS teachers? Do the institutional policies allow teachers to develop innovative teaching practices? The research was qualitative and the approach used was action research. The data collection instrument was the questionnaire. Due to the Covid-19 pandemic, it was not possible to carry out the survey in loco. The theoretical contribution that supports the study is based on the ideas and conceptions of Tardif, Zabala, Libâneo, Pimenta, and other authors. The research was carried out with twenty professors from the IFAM Campus Manaus Zona Leste, with three or more years of experience. As a research result, a synthesis of professional training knowledge, the experiential knowledge, and the teacher's conception about the students' integral human training was carried out. Through the research, it was possible to establish a relationship between the teachers' conceptions and the way they develop their work in the classroom. When analyzing the teaching knowledge, it was noticed the importance of classroom experience together with the academic formation, since the teacher's perception about the student is fundamental in the learning process. This aspect is even more important in an integral human formation, in which the educational projects developed at the institution help in this process. It was noticed, therefore, that the continuing education of educators is necessary so that they can improve even more in this regard. As part of the research, a portfolio was developed as an educational product, created from the main ideas found during the research, and with the aim of supporting continuing education in integral human education.